2016
DOI: 10.4269/ajtmh.16-0266
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostics for Soil-Transmitted Helminths

Abstract: Abstract. Historically, the diagnosis of soil-transmitted helminths (STHs) (e.g., Strongyloides stercoralis, Trichuris trichiura, Ancylostoma duodenale, Necator americanus, and Ascaris lumbricoides) has relied on often-insensitive microscopy techniques. Over the past several years, there has been an effort to use molecular diagnostics, particularly quantitative polymerase chain reaction (qPCR), to detect intestinal pathogens. While some platforms have been approved by regulatory bodies (e.g., Food and Drug Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 68 publications
(111 reference statements)
4
79
0
1
Order By: Relevance
“…Consistent with prior studies in low STH infection intensity settings, using qPCR led to substantial increases in hookworm detection and moderate increases in T. trichiura detection compared to 19,21,22,42). Poorer performance of Kato-Katz, particularly for hookworm, is likely due to rapid disintegration of hookworm ova following stool collection (42,52). However, we found that the detection rate for A. lumbricoides was 14% lower for qPCR than Kato-Katz.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with prior studies in low STH infection intensity settings, using qPCR led to substantial increases in hookworm detection and moderate increases in T. trichiura detection compared to 19,21,22,42). Poorer performance of Kato-Katz, particularly for hookworm, is likely due to rapid disintegration of hookworm ova following stool collection (42,52). However, we found that the detection rate for A. lumbricoides was 14% lower for qPCR than Kato-Katz.…”
Section: Discussionsupporting
confidence: 87%
“…A challenge in studies assessing accuracy of STH diagnostics is the lack of a gold standard diagnostic method (42). We thus used two different approaches to estimate sensitivity and specificity of each method, consistent with prior studies.…”
Section: Estimation Of Sensitivity and Specificitymentioning
confidence: 99%
“…Molecular methods like real-time PCR are increasingly used in the diagnosis of intestinal helminths (Verweij and Stensvold, 2014; O'Connell and Nutman, 2016). However, large-scale application of DNA detection procedures seems to be impaired, partly by the fact that the standard DNA extraction methods are not sufficient to release DNA from T. trichiura eggs (Demeler et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopy-based diagnostic methods are not sensitive at low intensity [73,74] and given that prevalence of infection is highly correlated with infection intensity, mean intensity is expected to be extremely low as populations approach the transmission breakpoint [2] and current microscopic methods would likely be inadequate for the documentation of transmission interruption. Although the assessment of novel diagnostics for STH is somewhat hampered by the lack of a gold standard [75], in field-based studies, quantitative polymerase chain reaction (qPCR) consistently detects more infections than microscopy-based methods. Using PCR as a pseudogold standard, these studies have found sensitivity of two-stool two-slide Kato-Katz as low as 70% for Ascaris and 32% for N. americanus relative to multiparallel qPCR [73], whereas sensitivity of sodium nitrate flotation was 83% for Ascaris and 34% for hookworm relative to multiplex PCR [73,76].…”
Section: Theoretical Possibilities: What Do the Models Tell Us?mentioning
confidence: 99%